The impact of the environmental approach and its implications for investment decisions. - HOUADEK, Issam; DJOUAD, Afaf (Journal of Human Sciences, 2020)
In the pursuit of improving development and enlarging the industrial base , the balance between the economical development and preserving the natural environment became one of the most important modernissues that needs to be taken into consideration when taking investment decision. Due to pollution operations, most of the investments took a turn that negatively affect human resources. As well as non compliance with environmental legislation, or the non existence of a comprehensive and effective system to implement these legislation. In addition to the absence of the adoption of integrated ecosystems to achieve conservation of human resources and to work on preventing pollution that results from the economical activities.